2011
DOI: 10.1101/gr.122044.111
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in radiation-induced cell death

Abstract: Radiation exposure through environmental, medical, and occupational settings is increasingly common. While radiation has harmful effects, it has utility in many applications such as radiotherapy for cancer. To increase the efficacy of radiation treatment and minimize its risks, a better understanding of the individual differences in radiosensitivity and the molecular basis of radiation response is needed. Here, we integrated human genetic and functional genomic approaches to study the response of human cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 33 publications
(40 reference statements)
1
23
0
Order By: Relevance
“…Our study found that exposure to radiation from CTA, like exposure to therapeutic doses of radiation (17, 18, 35, 36), activates biological pathways and genes and increases the activity of transcription factors involved in the regulation of cell repair, cell cycle progression, and apoptosis, which are critical in preventing the development of mutations, a finding that has not yet been previously reported. Although cells with DNA damage are mostly repaired, a small number of cells die after radiation exposure from CTA.…”
Section: Discussionsupporting
confidence: 55%
“…Our study found that exposure to radiation from CTA, like exposure to therapeutic doses of radiation (17, 18, 35, 36), activates biological pathways and genes and increases the activity of transcription factors involved in the regulation of cell repair, cell cycle progression, and apoptosis, which are critical in preventing the development of mutations, a finding that has not yet been previously reported. Although cells with DNA damage are mostly repaired, a small number of cells die after radiation exposure from CTA.…”
Section: Discussionsupporting
confidence: 55%
“…B cells can act as surrogate tissues whenever there is correlation between the expression levels of B cells and phenotypes of interest [20,21] and a large number of eQTLs originally identified in B cells can also be detected in multiple primary tissues [22,23]. Thus B-cells have been increasingly utilized for expression quantitative trait loci (eQTLs) studies [19,24] and as a cell model to assess gene expression responses [25]. While comprehensive mRNA expression data for human B-cells, obtained by RNA-seq, are available for this purpose [26], to date no such analysis was performed to identify miRNAs expressed in B-cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated individual variability in radiation sensitivity at the level of gene expression. 33, 34 Using genetic mapping, Smirnov et al identified individual polymorphisms in regulators of gene expression that contributed to individual differences in radiation sensitivity. 33 However, questions as to whether there is any genetic predisposition among certain patients affecting the cellular response to SPECT MPI, or whether these changes at both gene and protein levels reflect persistent DNA damage, are beyond the scope of the present study.…”
Section: Discussionmentioning
confidence: 99%